Effect of spin–phonon coupling on quantum correlation in the spin-1 XY model. (June 2021) - Lima, L.S.
Abstract: The XY model coupled with an external system as a phonon system may be studied in terms of its own variables only. Hence, the effect of phonons external in such system can be included in a general class of functionals of the coordinates of the system only. The specific form of this influence functional representing the effect of definite and random forces of a linear dissipative system and combination of these are analyzed in detail. Thus the effect of the spin–phonon interaction on entanglement is investigated where we obtain a small effect of the spin–phonon coupling on von Neumann entropy. Highlights: The spin-1 quantum one-dimensional XY model with spin–phonon interaction. The calculation of the von Neumann entropy employing the SCHA approximation. Influence of spin–phonon coupling on quantum correlation and quantum entanglement.